Interictal Dysphoric Disorder in Epilepsy and Its Relationship with Specific Clinical and Demographic Variables - Agata Maria Grzegorzewska; Mariusz Stanisław Wiglusz; Katarzyna Jakuszkowiak-Wojten; Wiesław Jerzy Cubała; Adam Włodarczyk; Joanna Szarmach (Psychiatry and Clinical Psychopharmacology)
Patients with epilepsy present a variety of psychiatric comorbidities, with mood disorders and anxiety disorders as well as interictal dysphoric disorder as the most frequent and often associated with comorbid mental conditions. Interictal dysphoric disorderand ictal and peri-ictal changes may contribute to overall clinical symptomatology in epilepsy, as well as subjective and objective adverse effects of anti-epileptic drugs. We performed a post-hoc analysis to verify the relation of interictal dysphoric disorder with specific clinical and demographic variables in people with epilepsy, including the correlation between interictal dysphoric disorder and anti-epileptic drugs. We found no correlation between the incidence of interictal dysphoric disorder and drug-resistant epilepsy, and no correlation between the incidence of interictal dysphoric disorder and sex was observed. The results of our analysis indicate that patients with interictal dysphoric disorder, compared with those with no interictal dysphoric disorder, had epilepsy onset at a later age, had had a history of psychiatric treatment and had distinctly lower, but not statistically significant, percentage of active employment status. Another finding was the frequent suicide attempts in people with epilepsy (11.5%). However, there was no relationship with interictal dysphoric disorder. We also did not find any evidence supporting the impact of epileptic medication on the incidence of interictal dysphoric disorder nor did the data contribute to support the evidence of interictal dysphoric disorder as a standing-alone phenomenon. An essential issue in epilepsy is awareness and understanding of interictal dysphoric disorder and concomitant mental health abnormalities as this is crucial for clinical practice and may significantly determine the progression and management of epilepsy if it remains ignored, and hence lead to a severe decline in life quality